Stepper motor control using pic microcontroller based on light intensity - Lau Aik Leng (School of Electrical System Engineering, University Malaysia Perlis, 2011)
These days the engineering system is an important part for a construction site and machinery to save the energy such as man-power. A lot of machinery types have been applies to saving times, money and power energy. One of the system is automatic machinery system which really helpful for human being especially to carrying the heavy things. Stepper Motor Control Using PIC Microcontroller Based on Light Intensity is a device that suitable for this project. The output is the performance of rotating of the stepper motor to carry the object. The system is powered by using AC to DC adapter. The main idea in this project is to create a system which that can provide a machinery for the human daily works. At the heart of project is a PIC 16F876A microcontroller which will be used as a brain of the system and control the system through a source code (C code) build using PIC C Compiler software or called PIC kits. In this project, it can control manually by human. So, it is really safety to use the stepper motor system for any industries.